KEPUASAN KERJA MEMEDIASI PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN CV. PRX DENPASAR - nurfayani, luh deviana angi; Wibawa, I Made Artha (E-Jurnal Manajemen; Vol 11 No 12 (2022), 2022)
This study aims to determine the role of job satisfaction in mediating the effect of perceived organizational support on employees organizational commitment. The number of samples used is 50 employees of CV. PRX Denpasar through the saturated sample method. Data collection was carried out through interviews and questionnaires. Data analysis technique used is classical assumption test, path analysis, and sobel test. The results of this study showed that perceived organizational support has a positive and significant effect on organizational commitment, perceived organizational support has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on organizational commitment, and job satisfaction partially mediates the effect of perceived organizational support on organizational commitment. The results of this study have implication for the management of CV. PRX Denpasar to pay more attention to indicators of perceived organizational support and employees job satisfaction, in order to increases employees organizational commitment. Keywords: Perceived Organizational Support; Job Satisfaction; Organizational Commitment